Produkcija diplomatskega védenja v jugoslovanski in poljski povojni diplomatski praksi (1945-1947) - Lukanc, Maja (Studia Historica Slovenica, 2020)
Diplomacy provides a unique insight into the socio-political circumstances of individual countries. Through their reports, analyses, and interpretations, diplomats shape a modicum of knowledge about the state in which they operate. Based on Yugoslav and Polish archival materials and memorial literature, the following contribution explores how diplomats from both countries contributed to the knowledge about Yugoslavia and Poland in the first years after World War II. The article takes into account the factors that influenced the production of knowledge in diplomacy and answers the question of whether the Yugoslav and Polish political decision-makers applied the newly acquired knowledge and how. The first post-war elections in both countries serve as a case study: they allowed diplomats to gain an insight into the operations of the local political elites; shed light on the attitude of the population towards the new authorities; and answered the question of how far the communists were willing to go in their struggle for power.
Keywords: 1945-1947; communism; diplomacija; diplomacy; elections; Jugoslavija; knowledge production; komunizem; Poland; politična zgodovina; Poljska; Svetovna vojna 1939-1945; volitve; Yugoslavia